ANALISIS KENDALA PENERAPAN BANGUNAN HIJAU DI INDONESIA - Yan Partawijaya; Wahyu Aktorina; Desmon Hamid (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
The construction and building sector have a crucial role in the economy and sustainable development in Indonesia. Green Buildings refer to buildings that pay attention to energy saving, proper water use, waste processing.The implementation of Green Buildings in Indonesia was launched in 2002 through Undang Undang No 28 tahun 2002 dan Peraturan Menteri PUPR No 21 tahun 2021 tentang Penilaian Kinerja Bangunan Hijau. The benefits of implementing Green Buildings include buildings that optimize energy use, utilize the environment to achieve good room quality such as air circulation and lighting, and process waste into something useful. Despite the many benefits of green buildings, the development of green building implementation in Indonesia is relatively slow. Barriers that cause the slow implementation of green buildings in Indonesia can be grouped into Financial, Regulatory, and Market Readiness issues. The parties responsible for encouraging the increased implementation of green buildings in Indonesia are categorized as Financial and Monetary, Private Business Entities, Organizations, and the Government. Strategies that can be implemented to encourage the increase in green buildings in Indonesia include Regulatory Adjustments, Building Mapping and Project Flow Creation, and Grants to Obtain Green Building Certification.